Youth, radio and Australian popular music policy - Wilson, Chris (Perfect Beat, 2014)
Following its extensive Australian Music on Radio Inquiry conducted between 1982 and 1988, the Australian broadcasting regulator concluded that commercial radio had a responsibility to support the development of Australian music but its own systems for ensuring they fulfilled that responsibility were insufficient. While, as an objective of broadcasting policy the support for Australian music intersected with the federal government’s interest in aiding the development of the local music industry, the government’s concurrent interest in deregulating the broadcasting sector impeded the ability of regulator to address its regulatory deficiencies. In this article I explore how the objective to encourage radio to support the development of the Australian music industry generated a key rationale for the development of non-commercial youth radio services that translated into establishment of the ABC Triple J youth radio network in the 1990s and a set of independent youth community radio stations in the early 2000s.